Analisa Penambahan Puree Buah NagaMerah (Hylocereus Polyrhizus) Terhadap Sifat Fisik dan Kimia Pada Produk Mie Basah Di Kabupaten Banyuwangi Tahun 2016 - Nanang Waludi; Imamatul Karimah; Mislan Mislan (JURNAL TEKNOLOGI PANGAN DAN ILMU PERTANIAN (JIPANG), 2019)
Banyuwangi geographically is the prosperous area and have a big potential fordevelopment increasing of agriculture product. Red dragonfruit ( HylocereusPolyrhizus) isone of superior comodity that is developed in Banyuwangi. Reddragonfruit contains 0,53 gof protein, 11,50 g of carbohydrate, 0,9 g of fiber, 0,139 g acid, Vitamin C and 9,4 mgbetakarotain, 134,50 mg calcium, 8,7 mg phosporus, 60,40 mg magnesium, and 90,20%water. The purpose of the research is to detect elongate value, standard of Vitamin C andnoodles fiber with increasing the puree of red dragonfruit. Method that is used to thisresearch is T-test. The result of this research got to shoe that puree concentration ofreddragonfruit within production of wet noodles is 15 %. The best elongate value to K1 andK3 treatment. Increasing puree of red dragonfruit is very significant e ffect to elongatevalue of noodles that be produced. In the K1 treatment value of elongate is 50% and K3 is57,3 %. Increasing puree of red dragonfruit is very significant effect to standard of VitaminC. In the wet noodles that be produced, the result that got sample of K1 is very highlysignificant with K3. Standard of Vitamin C in the sample of K1 is 7,45 mg/g and K3 is 21,72mg/g. Increasing puree of red dragonfruit is very significant to standard of noodles fiberthat be produced. The result that got is sample of K1 is very highly significant with K3.Standard of fiber in the K1 is 0,12% and K3 is 0,26%.